Ketuban Pecah Dini dengan Tingkat Asfiksia Bayi Baru Lahir - I Dewa Ayu Ketut Surinati (Jurnal Gema Keperawatan, 2014)
The purpose of this research is to know the relation between long premature rupture of membranes with rate of neonatal asphyxia. The methode of this research was analytic correlation with cross  sectional design. The samples were consisted of 72 respondents selected with retrosfektif sampling technique. Analysis of the data by Spearmen Rank Correlation test . The results of this study indicate that there was a significant relationship between duration of premature rupture of membranes with newborn asphyxia rate with p value 0,002 and r = 0,665.